THE INFLUENCE OF CULTURAL CONVENTIONS AND THE MARGINALIZATION OF WOMEN IN CHINESE CULTURE - Evellyn Graciella Wardhana; Luh Putu Krissiana Permata Dewi; I Made Lila Madhava (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2024)
This research focuses on identifying the women’s language features that influence the marginalization in Chinese culture especially women in Crazy Rich Asians Movie. The data was derived from Crazy Rich Asians (2018) movie through the documentation and observation method. Then the data collected was analyzed using the content analysis method based on the theory. Then the result of data analysis was presented descriptively. The results of this research found 12 sentence data containing women's language features. Meanwhile, the cultural dimensions found in the use of these maxims are General Particular, Situational Behavior, Intraorganistic and Extraorganistic.